Comparing developmental trajectories of elite able-bodied and wheelchair basketball players - Dehghansai, N.; Spedale, D.; Wilson, M. J.; Baker, J. (Adapted Physical Activity Quarterly, 2023)
Little is known about the factors influencing Paralympic athletes` journey to expertise and whether these athletes have trajectories similar to those of their able-bodied (AB) peers. The purpose of this project was to compare the developmental trajectories of wheelchair and AB basketball players. A total of 150 participants completed the Developmental History of Athletes Questionnaire. Results revealed that while AB athletes reached early career milestones at a significantly younger age, athletes with congenital impairments reached midcareer milestones at similar ages to AB athletes. In addition, athletes with acquired impairments were able to reach key late-career performance milestones (i.e., national and international debuts) at a similar age to the other two groups. The findings from this study suggest complex developmental pathways that may not be reflected in current developmental models. Therefore, the authors suggest that scientists and practitioners be cognizant of context-specific needs when providing training recommendations.